Effects of the cationic protein poly-L-arginine on airway epithelial cells in vitro - Shahida Shahana; Caroline Kampf; Godfried M. Roomans (Mediators of Inflammation)
Background: Allergic asthma is associated with an increased number of eosinophils in the airway wall. Eosinophils secrete cationic proteins, particularly major basic protein (MBP).